2022
DOI: 10.21203/rs.3.rs-2001945/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement of superconducting properties in the La–Ce–H system at moderate pressures

Abstract: Compressed polyhydrides have been regarded as an important platform for exploring high-temperature superconductors. The disordered states with high entropy could possess better superconducting properties than conventional periodic structures. Here, we have discovered a new high entropy superconducting La–Ce polyhydride (initial ratio La: Ce = 2.5–3.5:1), which is stable under low pressures with the giant enhancement of superconducting properties compared with the binary La-H and Ce-H system. Its superconductiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…22), La-Nd (ref. 23) and 24) binary alloys was studied, but without a noticeable enhancement in T c and pressure range of stability of presumably ternary final superhydrides compared with the parent binary Fm-3m-LaH 10 and P6 3 /mmc-LaH ~9-10 phases 8 .…”
mentioning
confidence: 99%
“…22), La-Nd (ref. 23) and 24) binary alloys was studied, but without a noticeable enhancement in T c and pressure range of stability of presumably ternary final superhydrides compared with the parent binary Fm-3m-LaH 10 and P6 3 /mmc-LaH ~9-10 phases 8 .…”
mentioning
confidence: 99%
“…Comparing these experimentally obtained cell volumes with previous experimental and theoretical results, we tentatively propose that the ratio of metal to hydrogen in the obtained compound is 1:10. Recently, our group also observed a hexagonal phase for the binary La–H system at 130 GPa, but the exact ratio is unknown [ 42 ]. According to the theoretical calculations for the binary La–H system, the P 6 3 /mmc -LaH 10 structure becomes thermodynamically favorable at pressures above ∼420 GPa; more importantly, this P 6 3 /mmc phase is also considered possibly metastable at low pressures and previous theoretical work has indicated that this phase was lying within the 20-meV/atom of the Fm \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} $\bar{3}$\end{document} m phase down to 150 GPa [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…29 Yet, thus far, only a few ternary hydrides have been experimentally synthesized, including the low- T c of BeReH 9 (7 K at 100 GPa) 30 and Li 5 MoH 11 (6.5 K at 160 GPa). 31 Recently, experimentalists have successfully synthesized several high- T c ternary hydrides (La,Y)H 10 (253 K at 183 GPa), 32 (La,Ce)H 9 (178 K at 110 GPa or 176 K at 100 GPa) 33,34 and (La,Nd)H 10 (148 K at 170 GPa), 35 which further demonstrates the superconductive potential of ternary hydrides. Of these, superconductors based on sulfur hydride have been abundantly reported, such as C–S–H, 36–39 Y–S–H, 40,41 Se–S–H, 42 B–S–H, 43 Fe–S–H, 44 Ca–S–H, 45 even including noble gases like Xe–S–H.…”
Section: Introductionmentioning
confidence: 94%